Development of a universal kit for rapid detection of aggressive chemicals, rocket fuel components and uranium components and uranium compounds in various environments - Pashinin Valery A.; Popov Vladimir G.; Sukhov Philip I.; Ulianova Oksana A. (E3S Web of Conferences, 2023)
The materials of the article are devoted to the issues of ecology and safety at enterprises and railway transport. The urgency of developing a universal kit for rapid detection of aggressive chemicals, rocket fuel components and uranium compounds in various environments is due to the fact that the presence on the surface and in water can lead to poisoning and chemical burns of working personnel and the public. It is also caused by the need to make managerial decisions when eliminating the consequences of accidents at food and related industries. The article discusses the methods of rapid detection of aggressive chemicals and suggests scientific, methodological and technological approaches to the development of a universal set of tools for group rapid detection of aggressive chemicals and uranium compounds in water and on the surfaces of objects using aerosol devices with original indicator formulations. The place of research is Moscow and the Moscow region